An Architecture and Query Language for a Federation of Heterogeneous Dictionary Databases. - Patrick, Jon; Zhang, Jun; Artola-Zubillaga, Xabier (Computers & the Humanities, 2000)
An architecture for federating heterogeneous dictionary databases is described. It proposes a common description language and query language to provide for the exchange of information between databases with different organizations, on different platforms and in different DBMSs. The common query language has an SQL like structure. The first version of the description language follows the TEI standard tag definitions for dictionaries with the expectation that the description language will be expanded in the future. A practical implementation of the proposals using WWW technology for two multi-lingual dictionaries is described.